On assemblages and things: fluidity, stability, causation stories and formation stories - Timothy Rutzou; Dave Elder-Vass (2019)
This paper conducts a dialogue, and creates a new synthesis, between two of the most influential ontological discourses in the field of sociology: assemblage theory and critical realism. The former proposes a focus on difference, fluidity and process, the latter a focus on stability and structure. Drawing on and assessing the work of Deleuze, DeLanda and Bhaskar, we argue that social ontology must overcome the tendency to bifurcate between these two poles and instead develop an ontology more suited to explaining complex social phenomena by accommodating elements of both traditions. Going beyond DeLanda’s recent work, we argue that a concept of causal types must be employed alongside a typology of structures to give us an ontology that can sustain sociology’s need for both formation stories and causation stories. We illustrate the necessity and value of our proposed synthesis by discussing MacKenzie’s recent empirical analysis of a high frequency trading firm.